2003
DOI: 10.1007/s00330-003-1888-6
|View full text |Cite
|
Sign up to set email alerts
|

Classification of calcaneal fractures by spiral computed tomography: implications for surgical treatment

Abstract: The purpose of this study was to evaluate spiral computed tomography and multislice CT (SCT/MSCT) with multiplanar reconstructions (MPR) in the classification of calcaneal fractures according to a modified CT classification and to quantify fragment displacement to guide surgical treatment. Forty-eight calcaneal fractures were examined by spiral CT (1- to 2-mm slice thickness, pitch=1.5) with multiplanar reconstructions (MPR). Fractures were grouped according to a modified Munich classification scheme, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In cases of injury, the calcaneus is initially visualized with medio-lateral and axial XR. However, CT imaging is also used in the diagnosis (22). CT displays the characteristics of fracture lines and displacement of fractures better than XR (23).…”
Section: Discussionmentioning
confidence: 99%
“…In cases of injury, the calcaneus is initially visualized with medio-lateral and axial XR. However, CT imaging is also used in the diagnosis (22). CT displays the characteristics of fracture lines and displacement of fractures better than XR (23).…”
Section: Discussionmentioning
confidence: 99%
“…The inappropriate surgical scar healing may lead to wound breakdown in calcaneum fractures [6][7][8][9][10][11][12][13][14][15][16][22][23][24] [26]. Their results showed that locking plates could In this study, we have followed Sanders classifi cation, which is CT, based.…”
Section: Discussionmentioning
confidence: 99%
“…Calcaneal fractures are divided into two major categories, intraarticular and extraarticular. Accurate description of calcaneal fractures, including the position and displacement of fracture fragments, is extremely useful to surgeons, with signifi cant implications for the management of these fractures [10].…”
Section: Mechanism Of Injury Fracture Type and Classifi Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial imaging typically consists of a 3-view study, with the possibility of additional views as indicated by the clinical setting [11]. CT is commonly used in evaluating the true extent of osseous injury in complex fractures, and at times is used as the initial medical imaging study in polytrauma patients, and in complex regions, such as the midfoot [12][13][14]. In polytrauma patients, approximately 25% of foot fractures identified on CT are overlooked on radiographs [12].…”
Section: Overview Of Imaging Modalitiesmentioning
confidence: 99%